EFEKTIVITAS METODE WAFA SEBAGAI INOVASI DALAM PEMBELAJARAN MEMBACA AL-QUR’AN DI TPQ AL-IKHLASH PALA’AN NGAJUM MALANG - Achadah, Alif; Aziza, Ilma Fahmi; Hasanah, Siti Muawanatul (Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2020)
In Islamic religious education, the Qur'an is a source that is used as the foundation of the Islamic religion. Therefore, the Qur'an has an urgent position in guiding and directing people in their daily lives. However, there is a large gap between the importance of reading the Qur'an with the ability to read the Qur'an in Muslim communities in Indonesia. . The Chancellor of the al-Qur'an Institute of Higher Education (PTIQ) Jakarta, Nazaruddin Umar assessed that people who are illiterate al-Qur'an are still high in Indonesia. therefore it is necessary to apply effective and innovative methods of learning the the al-Qur'an. The supporting factors for the application of the waqa method include: the material taught is not much different from the material that has usually been studied, the TPQ Al-Ikhlash assistants help researchers during the process of applying the